Effects of Different Concentrations of Lactobacillus plantarum and Bacillus licheniformis on Silage Quality, In Vitro Fermentation and Microbial Community of Hybrid Pennisetum - Yanchen Zhu; Haoming Xiong; Zhiying Wen; Hanchen Tian; Yiye Chen; Longfei Wu; Yongqing Guo; Baoli Sun (Animals, 2022)
The purpose of the experiment was to study the effects of different concentrations of Lactobacillus plantarum (LP) and Bacillus licheniformis (BL) on the quality of hybrid Pennisetum (HP) silage. The experiment consisted of five treatment groups. The control group did not use additives, and the experimental groups were added with LP or BL of 1 × 105 cfu/g fresh weight (FW) and 1 × 107 cfu/g FW, respectively. The results showed that LP and BL could increase the in vitro fermentation gas production and reduce the ammonia nitrogen (AN) content in HP silage. Water-soluble carbohydrates (WSC), lactic acid (LA) content, and gas production in the LP group were positively correlated with LP addition, and acetic acid (AA) was negatively correlated with addition. The content of WSC and LA in the LP7 group was significantly higher than that in the control group (p < 0.05), and AA was lower than that in the control group (p > 0.05). Dry matter (DM), crude protein (CP), and gas production were negatively correlated with the addition of BL, while acid detergent fiber (ADF) content was positively correlated with the addition of BL. Furthermore, in the above indicators, the BL5 group reached a significant level with the control group (p < 0.05). The results of 16sRNA showed that the use of LP and BL could increase the relative abundance of Lactobacillus and decrease the relative abundance of Weissella in HP silage compared with the control group. In conclusion, LP and BL can significantly improve the quality of HP silage. The LP7 group and the BL5 group have the best silage effect. From the perspective of gas production in in vitro fermentation, the LP7 group had stronger fermentability and higher nutritional value.